2021
DOI: 10.3390/ijerph18168811
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion and Rumination Type Mediate the Relation between Mindfulness and Parental Burnout

Abstract: The COVID-19 lockdown increased the day-to-day challenges faced by parents, and thereby may have increased parental burnout risk. Therefore, identifying parental burnout protection factors is essential. This study aimed to assess the protective role of the following factors which can be increased through mindfulness practice: trait mindfulness, self-compassion, and concrete vs. abstract ruminations. A total of 459 parents (Mage = 40; 98.7% female) completed self-reported questionnaires at two-time points to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 77 publications
4
38
0
Order By: Relevance
“…It provides an important perspective because it shows alternative ways of influencing therapy or family support. By effectively preventing stress and parental burnout, family functionality can be reinforced in various areas (e.g., communication, organization of family life, care, and rehabilitation) [39,40]. At the same time, by modifying the functioning of the family system, one can expect beneficial changes in the parents' disposition and an increase in their ability to cope with problems.…”
Section: The Influence Of Family Functionmentioning
confidence: 99%
“…It provides an important perspective because it shows alternative ways of influencing therapy or family support. By effectively preventing stress and parental burnout, family functionality can be reinforced in various areas (e.g., communication, organization of family life, care, and rehabilitation) [39,40]. At the same time, by modifying the functioning of the family system, one can expect beneficial changes in the parents' disposition and an increase in their ability to cope with problems.…”
Section: The Influence Of Family Functionmentioning
confidence: 99%
“…It is believed to be an important factor in the development of depression, impaired physical and mental health, and an increase in work-related burnout ( 21 23 ). Numerous studies have also emphasized the positive mediating role of rumination in emotional exhaustion ( 24 ). Affective rumination continuously consumes cognitive and emotional resources.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Research has identified several protective factors against parental burnout: emotional competencies (Bayot et al, 2021;Lin et al, 2021a;Lin et al, 2021b); mindfulness, selfcompassion, concrete ruminations (Paucsik et al, 2021); and low levels of perfectionism (Kawamoto et al, 2018;Sorkkila & Aunola, 2020). The studies included in the present meta-analyses address some of these competencies.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, based on exploratory and descriptive studies, parental burnout syndrome has been defined by the research . Subsequently, causality based studies aimed to identify risk and protective factors from parental burnout (Paucsik et al, 2021) as well as the extent to which psychological interventions can contribute to the reduction of parental burnout .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation